Content Structure of the Subject «Self-Cognition» in the Conditions of the Renewed Content of Education (Journal of Educational Sciences, 2020)
It is examined the content structure of the subject “Self-сognition” in the context of the updatedcontent of education in general education schools in the article. The analysis of textbooks and educational-methodical complexes of the subject is carried out, the authors give a methodological descriptionof the 6th grade textbook.The article also reflects the regulatory documents that served as the basis for the preparation oftextbooks in the discipline. When analyzing textbooks and educational-methodological complexes, theauthors rely on the stages in the development and formation of the subject and, thus, strive for a methodologicalanalysis of textbooks in the context of the updated content of education, showing the continuityof the development of the content of the subject, and clearly indicating the novelty of the approach.The article provides tables for analyzing the content of textbooks at the primary, basic, senior levelof the school. Separate attention is paid to the position of the teacher in teaching self-сognition - an opendialogue between teacher and a pupil in the classroom.The role of the teacher in the formation of the inner and personal concept of “I” of each pupil isspecial. Thinking with children, rejoicing together, grieving together, learning something new together,being surprised and worried together, which not only creates a positive atmosphere in the classroom, butalso helps pupils understand the realities of life.As examples, the authors use some tasks from the textbook and analyze the methodological aspectsof new methods of teaching the subject. The research is funded by the Science Committee of the Ministryof Education and Science of the Republic of Kazakhstan (Grant No. AP08856223).Key words: updated content of education, self-knowledge, spiritual and moral education, textbook,student’s notebook, methodological guide, content of education.